Crushing of patterned shells - Lim, Tariene Zi Yi. (2012)
This project aims to design and analyze the energy absorption capabilities of various patterns on shells. The patterns tested were a trapezium and a pair of rectangles, placed on the center or a fixed distance apart. The project primarily on square shells was extended to hexagonal shell. Under quasi-static axial loading, a conventional square tube folds into six sections. Thus, each square tube was divided into six sections, and one pattern will be cut on each section of the tube, on each side of the square. The hexagonal tube on the other hand, folds into five sections. Hence there is five of each pattern cut on each side of the hexagon. The patterns on the shells are placed at the center of each section, and are symmetrical about the center line for consistency.